A construção de identidades em inscrições urbanas: uma investigação semiótica das inscrições feitas nos campi do Centro de Humanidades da UFC - Cabral, Susy Anne Almeida (2018)
This study aims to analyze, according to Greimasian semiotics, the construction of discursive identities on five examples of street art which were made in different campuses of Humanities courses by different producers. Our goal is to investigate the emergence of an identity that is common to all the texts, so that we can say there is an archi-identity of these enunciators based on this semiotic practice, which is the practice of street art production. Moreover, we think this identity can also be understood as an identity of the practice itself. To achieve this goal this work was made according to discoursive semiotics, as already said, because this theory understands that the identity of a subject is built in the enunciation act, which means that the image is a result of the discourse. In addition to the classical authors of this semiotic theory, our work is based on Fontanille (2005) and Correa (2016). The first one gives us the conception that semiotic processes can be recognized in our natural and/or cultural world as actantial structures, so that we can analyze them according to the Greimasian concept of lato sensu narrativity (LEITE, 2017). The second one enables us to name the several street art manifestations at the campuses as urban inscriptions, independent of the materiality and the support they have. We investigate if there is, inside of this narrativity, a semiotic coherence that can be understood as common to all the enunciators and to the practice of urban inscriptions at the campuses. We conceive therefore the urban inscriptions as semiotic objects which emerge inside of a specific semiotic practice. This practice constitutes a simulacrum and a form of life. In relation to our corpus, this form of life is characterized as transgressive.